The Impact of Customer Service Quality and Mobile Transactions in Increasing Customer Confidence at LPD Badung District - Kadek, Krisnawati Ni; Nyoman, Usadha I Dewa; Putu, Yuli Tresna Dewi Ni (International Journal of Management and Business Intelligence, 2024)
This study uses the Badung Regency Village Credit Institution as its focal point. The purpose of the study is to find out how consumer trust in the Village Credit Institution in Badung Regency is impacted by service quality and mobile transactions. quantitative multiple regression research method with SPSS Version 24 for data interpretation and an example of 93. Research Results: (1) Mobile transactions (X2) have a positive and significant effect on customer trust; (2) customer trust (Y) has a simultaneous positive and significant effect on quality of service and mobile transactions, so that they become one unit in the LPD in Badung Regency; and (3) customer trust (X1) has a favorable and noteworthy increasing impact on customer trust. Implications for Research According to this study, mobile transactions and factors pertaining to service quality have a significant impact on Badung Regency's Village Credit Institutions.